Dark Energy Survey Year 1 Results: calibration of redMaGiC redshift distributions in DES and SDSS from cross-correlations. Issue 2 (3rd September 2018) - Cawthon, R; Davis, C; Gatti, M; Vielzeuf, P; Elvin-Poole, J; Rozo, E; Frieman, J; Rykoff, E S; Alarcon, A; Bernstein, G M; Bonnett, C; Rosell, A Carnero; et al.
ABSTRACT: We present calibrations of the redshift distributions of redMaGiC galaxies in the Dark Energy Survey Year 1 (DES Y1) and Sloan Digital Sky Survey (SDSS) DR8 data. These results determine the priors of the redshift distribution of redMaGiC galaxies, which were used for galaxy clustering measurements and as lenses for galaxy–galaxy lensing measurements in DES Y1 cosmological analyses. We empirically determine the bias in redMaGiC photometric redshift estimates using angular cross-correlations with Baryon Oscillation Spectroscopic Survey (BOSS) galaxies. For DES, we calibrate a single-parameter redshift bias in three photometric redshift bins: $z$ ∈ [0.15, 0.3], [0.3, 0.45], and [0.45, 0.6]. Our best-fit results in each bin give photometric redshift biases of |Δ$z$ | < 0.01. To further test the redMaGiC algorithm, we apply our calibration procedure to SDSS redMaGiC galaxies, where the statistical precision of the cross-correlation measurement is much higher due to a greater overlap with BOSS galaxies. For SDSS, we also find best-fit results of |Δ$z$ | < 0.01. We compare our results to other analyses of redMaGiC photometric redshifts.